Chinese Cultural Representation and Global Identity in the Movie Over the Moon (2020) - Arta, Imelda Indry; Rafael, Adrian David; Nuraini, Tantri (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
This study examines how “Over the Moon” (2020), a Sino-American animated film co-produced by Netflix and Pearl Studio, represents Chinese cultural identity within a globalized media landscape. Using a qualitative descriptive approach with semiotic and cultural analysis, the research focuses on how traditional Chinese symbols, myths, and values are visually and narratively constructed within the film. Guided by Barthes’ semiotic model and Hall’s representation theory, the analysis identifies key cultural signifiers—such as the moon goddess Chang’e, familial devotion, and the Mid-Autumn Festival—and interprets how these are transformed to align with global storytelling aesthetics. The findings reveal that “Over the Moon” synthesizes cultural authenticity and global accessibility through a hybrid mode of representation that preserves essential aspects of “Chineseness” while adapting them for international audiences. This interplay between localization and universalism illustrates how globalization shapes the rearticulation of Chinese identity in contemporary animation.